AB0015 Capture of iga immune complexes and enrichment in iga ig gene expression both suggest a role for fcrl4+ b cells in the link between mucosal and joint inflammation. (15th June 2017) - Cameron, J; Clay, E; Amara, K; Sippl, N; Filer, A; Raza, K; Malmström, V; Scheel-Toellner, D
Abstract : Background: Increasing evidence points to the autoimmune process of rheumatoid arthritis (RA) originating at mucosal surfaces. Previous work from our group described a subset of B cells in the synovium and synovial fluid (SF) of RA patients which can be distinguished by their expression of the Fc-like receptor 4 (FcRL4) and elevated expression of RANKL, indicating a unique pathogenic function 1, 2 . B cells expressing FcRL4 were originally described as a distinct memory B cell subset in human tonsils where they accumulate in the epithelium 3 . We have recently shown that they are enriched in cells recognizing citrullinated autoantigens (Amara, K. et al. under revision). Recent in vitro work suggested that FcRL4 is a low affinity receptor for aggregated IgA 4 . Objectives: 1) To investigate the interaction of RA synovial fluid FCRL4+ B cells with IgA 2) To examine the distribution of Ig classes by flow cytometry and PCR Methods: SF mononuclear cells were isolated, labelled for FcRL4, IgA and CD19 and analysed by flow cytometry. In experiments identifying IgA B cell receptors, SF mononuclear cells were briefly incubated in an acidic buffer to remove surface receptor bound antibodies before staining. Heat-aggregated purified human IgA was added to assess IgA binding to FcRL4+ B cells. Single B cells were sorted from SF of RA patients and their constant region genes probed for identification of their Ig subclass by PCR. Results: Ex vivo, FcRL4 + B cells in SF of RA patients have a higher load of IgA bound to their surface compared to their FcRL4- counterparts. After in vitro removal of surface bound IgA, they can bind heat-aggregated IgA (p=0.0313). We also demonstrate that a significantly higher proportion of FcRL4+ B cells use IgA BCRs (p=0.0061) by flow cytometry and further more by probing constant region genes by PCR an enrichment for Ig genes for coding the IgA1 isotype (p=0.009) was found. Conclusions: Both their ability to capture IgA immune complexes through binding to FcRL4 and their enrichment in IgA Ig gene expression suggest a potential role for synovial fluid FcRL4 + B cells in the mucosal origin of joint inflammation. References: Yeo, L. et al. Cytokine mRNA profiling identifies B cells as a major source of RANKL in rheumatoid arthritis. Ann Rheum Dis 70, 2022–2028, doi:10.1136/ard.2011.153312 (2011). Yeo, L. et al. Expression of FcRL4 defines a pro-inflammatory, RANKL-producing B cell subset in rheumatoid arthritis. Ann Rheum Dis 74, 928–935, doi:10.1136/annrheumdis-2013–204116 (2015). Falini, B. et al. Expression of the IRTA1 receptor identifies intraepithelial and subepithelial marginal zone B cells of the mucosa-associated lymphoid tissue (MALT). Blood 102, 3684–3692, doi:10.1182/blood-2003–03–0750 (2003). Wilson, T. J., Fuchs, A. & Colonna, M. Cutting edge: human FcRL4 and FcRL5 are receptors for IgA and IgG. J Immunol 188, 4741–4745, doi:10.4049/jimmunol.1102651 (2012). Disclosure of Interest: None declared